The decline in youth drinking in England—is everyone drinking less? A quantile regression analysis. (1st December 2019) - Oldham, Melissa; Callinan, Sarah; Whitaker, Victoria; Fairbrother, Hannah; Curtis, Penny; Meier, Petra; Livingston, Michael; Holmes, John
Abstract: Background and Aims: Youth alcohol consumption has declined significantly during the past 15 years in many high‐income countries, which may have significant public health benefits. However, if the reductions in drinking occur mainly among lighter drinkers who are at lower risk, then rates of alcohol‐related harm among young people today and adults in future may not fall in line with consumption. There is conflicting evidence from Swedish school studies, with some suggesting that all young people are drinking less, while others suggest that alcohol consumption among heavier drinkers may be stable or rising while average consumption declines. This paper extends the geographical focus of previous research and examines whether the decline in youth drinking is consistent across the consumption distribution in England. Design: Quantile regression of 15 waves of repeat cross‐sectional survey data. Setting: England, 2001–16. Participants: A total of 31 882 schoolchildren (50.7% male) aged 11–15 who responded to the Smoking Drinking and Drug Use among Young People surveys. Measurements: Past‐week alcohol consumption in UK units at each fifth percentile of the consumption distribution. Findings: Reductions in alcohol consumption occurred at all percentiles of the consumption distribution analysed between 2001 and 2016, but the magnitude of the decline differed across percentiles. The decline in consumption at the 90th percentile [β = −0.21, confidence interval (CI) = −0.24, −0.18] was significantly larger than among either lighter drinkers at the 50th percentile (β = −0.02, CI = −0.02, −0.01) or heavier drinkers at the 95th percentile (β = −0.16, CI = −0.18, −0.13). Conclusions: Alcohol consumption among young people in England appears to be declining across the consumption distribution, and peaks among heavy drinkers. The magnitude of this decline differs significantly between percentiles of the consumption distribution, with consumption falling proportionally less among the lightest, moderate and very heaviest youth drinkers.